2017
DOI: 10.1111/jocn.13576
|View full text |Cite
|
Sign up to set email alerts
|

Two years of unintended consequences: introducing an electronic health record system in a hospice in Scotland

Abstract: Aims and objectives To explore the impact of implementing an electronic health record system on staff at a Scottish hospice. Background Electronic health records are broadly considered preferable to paper‐based systems. However, changing from one system to the other is difficult. This study analysed the impact of this change in a Scottish hospice. Design Naturalistic prospective repeated‐measures mixed‐methods approach. Methods Data on the usability of the system, staff engagement and staff experience were obt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
4

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 47 publications
0
15
0
4
Order By: Relevance
“…Team dynamics play a substantial role in the success of any initiative (Snowden & Kolb, ). Initially the research team had hoped that if one or two members of the nursing team reported positive experiences of recruitment then it might encourage others to engage.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Team dynamics play a substantial role in the success of any initiative (Snowden & Kolb, ). Initially the research team had hoped that if one or two members of the nursing team reported positive experiences of recruitment then it might encourage others to engage.…”
Section: Resultsmentioning
confidence: 99%
“…The method has successfully been used in previous studies designed to better understand satisfaction in childbirth (Hollins‐Martin, Snowden, & Martin, ; Snowden et al., ), the process of becoming competent as a nurse prescriber (Snowden, ; Snowden & Martin, ,b) and the process of organizational change associated with implementing an electronic health record (Snowden & Kolb, ). It is a pragmatic method of synthesizing primary data with literature to produce more generalizable results than doing either alone (Snowden & Martin, ,b).…”
Section: The Studymentioning
confidence: 99%
“…Data quality and data use interventions in high-income countries heavily relied on the use of technology. Examples are the use of electronic medical or health record systems to improve data quality [57][58][59][60][61] and approaches to enhance the interoperability of such data sources to enhance the availability of data and use [58,60,62,63]. At the same time, these interventions were target-specific compared to the interventions in low-and middle-income countries, where targets were broader.…”
Section: Discussionmentioning
confidence: 99%
“…(8) Em estudos nacionais e internacionais a incompatibilidade de sistemas de informação em relação ao processo de trabalho em saúde, bem como a sua complexidade de uso foram fatores que contribuíram para o seu insucesso e com repercussões negativas sobre a gestão e assistência. (1)(2)5,(10)(11) O desenvolvimento de tecnologias da informação deve ser adequado às necessidades informacionais de seus potenciais usuários, além de contribuir para a gestão das informações que emergem do processo de trabalho. (12)(13) Para ser amplamente adotada como uma tecnologia inovadora,deve instrumentalizar as pessoas com vistas a qualificar o fluxo de informações, o planejamento e a tomada de decisões assertiva, pois do contrário tende a ser rejeitada.…”
Section: [] a Implantação Está Acontecendo A Toque De Caixa O Queunclassified
“…(2,(12)(13)(14) Além disso, a gestão do cuidado também tem sido prejudicada quando da utilização inadequada de sistemas de informação, acarretando impactos negativos sobre a segurança do paciente, famílias e comunidades. (11,15) A subutilização não pode ser repetida com os sistemas de software da estratégia e-SUS AB, pois a sua principal premissa é proporcionar a gestão da informação voltada para o planejamento e a tomada de decisões locais. (3,5) Espera-se que a utilização dos sistemas de software da estratégia e-SUS AB favoreçam a sistematização de dados, desde a coleta até a análise das informações, instrumentalizando a organização do trabalho e a gestão do cuidado.…”
Section: [] a Implantação Está Acontecendo A Toque De Caixa O Queunclassified